ANALYZING THE RELATIONSHIP BETWEEN HEALTH RESOURCES DISTRIBUTION AND ECONOMIC GROWTH IN CHINA - Morris, Elizabeth (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
This study examines the dynamic relationship between health resource allocation and regional economic development in various provinces of China. Health resources are vital for ensuring the physical health of the population, which in turn is essential for fostering economic growth. Recent trends in the distribution of health resources have shown significant spatial differentiation, though the gap in regional economic development has been narrowing. The study reveals that the balanced development of the regional economy has helped reduce disparities in health resource allocation. However, challenges persist due to factors like limited investment channels, resource training cycles, and insufficient local finances in some economically underdeveloped regions. The research focuses on evaluating the coordination between health resources and regional economies, providing insights into the synchronized advancement of these two critical systems. It aims to contribute to the high-quality development of the health economy, ultimately promoting the physical well-being and economic prosperity of the population.